2022
DOI: 10.3390/epidemiologia3040038
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccination: Sociopolitical and Economic Impact in the United States

Abstract: Since the outbreak of COVID-19, vaccination against the virus has been implemented and has progressed among various groups across all ethnicities, genders, and almost all ages in the United States. This study examines the impacts of socioeconomic status and political preference on COVID-19 vaccination in over 443 counties in the southwestern United States. Regression analysis was used to examine the association between a county’s vaccination rate and one’s personal income, employment status, education, race an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
1
1
Order By: Relevance
“…[26][27][28][29] However, our study did not identify any demographic subgroup that was more or less vaccinated. This is in contrast with many US-based studies that have found higher rates of vaccination in the elderly, [7] Caucasian and Asian communities, [30][31][32] and regions with high insurance coverage. [33,34] Many studies have also found lower rates of immunization in African Americans, nonwhite Hispanics, [31,35] and patients with no insurance, housing instability, food insecurity, conservative political views, and education restricted to a high-school diploma or less.…”
Section: Discussioncontrasting
confidence: 96%
“…[26][27][28][29] However, our study did not identify any demographic subgroup that was more or less vaccinated. This is in contrast with many US-based studies that have found higher rates of vaccination in the elderly, [7] Caucasian and Asian communities, [30][31][32] and regions with high insurance coverage. [33,34] Many studies have also found lower rates of immunization in African Americans, nonwhite Hispanics, [31,35] and patients with no insurance, housing instability, food insecurity, conservative political views, and education restricted to a high-school diploma or less.…”
Section: Discussioncontrasting
confidence: 96%
“…Finally, the main current challenge is to obtain herd immunity and “vaccine equity” among countries, bearing in mind that the challenges of vaccines against COVID-19 include three dimensions, ranging from development and dissemination to the distribution of vaccines [ 74 , 75 ]. Vaccine distribution is still a problem in countries with low human development, which still lack vaccines and strategies to exceed the target of 70% of the population vaccinated [ 76 , 77 ].…”
Section: Discussionmentioning
confidence: 99%